Evaluation monitoring and accompaniment of the training process in RTC: theoretical-practical and operational aspects - Kátia Cristina Custódio Ferreira Brito; Adaires Rodrigues de Sousa; Roberto Francisco de Carvalho (Universidade Federal do Norte do Tocantins, 2021)
The article at stake approaches thematic related to the evaluation, monitoring and accompaniment of the Rede ColaborAção Tocantins (RCT) developed in the pandemic period. The present reflection has objective to problematize the instrumental conception of the education and the evaluation by means of theoretician-philosophical reflection, which understands the education as social práxis, based on principles of the democratic management and the substantive formation. The study which originated this text was carried through in the perspective critical-dialectic, starting from the empirical reality understood as complex reality, contradictory and mediatized by multiples determinative. The study provided - as a theoretical-practical result - the explanation of the philosophical, political and methodological foundations of evaluation, monitoring and follow-up in the instrumental and substantive perspectives, as well as this enabled the composition of a set of criteria and procedures applicable to training in municipal education management. The discussion includes, in addition to the theoretical and practical aspects of management, evaluation, monitoring and accompaniment, the practical operational aspects of the training process.